Family law with skills ten years later: Experiential education in the introductory family law course. (20th October 2022) - Schepard, Andrew
Abstract: Hofstra's Law School's Family Law with Skills Course (FLWS) incorporates experiential education into an introductory family law course. This article describes FLWS' recent experiential curricular innovations: (1) a transition to online learning; (2) the Navigator Program in which students provide legal information (in contrast to legal advice) to self‐represented litigants in divorce actions; (3) a forum with leadership from the divorce bar nationwide that introduces law students to the nature and future of family law practice; and (4) a divorce representation simulation in which law students counsel a client with consulting help from a psychologist, asset valuator and dispute resolution expert. This article describes the contribution each of these innovations makes to the education of family law students and how they are organized. It concludes that experiential education should be part of the education of future family lawyers in the interests of improving the quality of the representation they provide and their commitment to the field. Key points for the family court community: Hofstra Law School's Family Law with Skills (FLWS) course integrates teaching of traditional family law doctrine with experiential learning. Recent innovations in FLWS' experiential education activities involving stakeholders in the family court community include: Integration of remote learning to enable guest participation by family lawyers and other stakeholders in providing feedback on student performances from anywhere, and conveys to students that their technological skills will be an advantage in their future practice. Town hall forums with leaders from the practicing family law bar that broaden student perspectives on the nature and future of family law practice. A Navigator Program in which law students provide legal information to self‐represented divorce litigants to help complete required forms. A focus on developing student counseling skills, a central function of family lawyers. Students draft a counseling plan for a simulated divorce client. Prior to doing so they engage in interdisciplinary consultations with experts in mental health, asset valuation and dispute resolution They also receive feedback on simulated counseling performances from experienced family lawyers and mediators. Ten years of experience with FLWS establishes that integration of experiential learning into the basic family law course is feasible and improves student understanding of family law doctrine and the nature of family law practice. Experiential education encourages students to understand the satisfactions and challenges of representing family law clients and to value the professionals who are part of the modern family law system.